Trends of Incidence, Mortality, and Future Projection of Spinal Fractures in Korea Using Nationwide Claims Data - Kim, Tae-Young; Jang, Sunmee; Park, Chan-Mi; Lee, Ahreum; Lee, Young-Kyun; Kim, Ha-Young; Cho, Eun-Hee; Ha, Yong-Chan (Journal of Korean medical science, 2016)
Spinal fractures have been recognized as a major health concern. Our purposes were to evaluate the trends in the incidence and mortality of spinal fractures between 2008 and 2012 and predict the number of spinal fractures that will occur in Korea up to 2025, using nationwide data from the National Health Insurance Service (NHIS). A nationwide data set was evaluated to identify all new visits to medical institutes for spinal fractures in men and women aged 50 years or older between 2008 and 2012. The incidence, mortality rates and estimates of the number of spinal fractures were calculated using Poisson regression. The number of spinal fractures increased over the time span studied. Men and women experienced 14,808 and 55,164 vertebral fractures in 2008 and 22,739 and 79,903 in 2012, respectively. This reflects an increase in the incidence of spinal fractures for both genders (men, 245.3/100,000 in 2008 and 312.5/100,000 in 2012; women, 780.6/100,000 in 2008 and 953.4/100,000 in 2012). The cumulative mortality rate in the first year after spinal fractures decreased from 8.51% (5,955/69,972) in 2008 to 7.0% (7,187/102,642) in 2012. The overall standardized mortality ratio (SMR) of spinal fractures at 1 year post-fracture was higher in men (7.76, 95% CI: 7.63-7.89) than in women (4.70, 95% CI: 4.63-4.76). The total number of spinal fractures is expected to reach 157,706 in 2025. The incidence of spinal fractures increased in Korea in the last 5 years, and the socioeconomic burden of spinal fractures will continue to increase in the near future.